The one God : a critically developed evangelical doctrine of trinitarian unity - Chiavone, Michael L (Eugene, Or. : Pickwick Publications, 2009)
"Seeks to develop an understanding of the unity of the Triune God by examining the positions put forward by Karl Rahner, Millard Erickson, John Zizioulas, and Wolfhart Pannenberg."--P. [4] of cover
Includes bibliographical references (p. 223-232)
Keywords: Rahner, Karl, -- 1904-1984 -- Contributions in doctrine of the Trinity; Erickson, Millard J. -- Contributions in doctrine of the Trinity; Zizioulas, Jean, -- 1931- -- Contributions in doctrine of the Trinity; Pannenberg, Wolfhart, -- 1928- -- Contributions in doctrine of the Trinity; Trinity -- History of doctrines -- 20th century